Day-ahead and intra-day economic dispatch of electricity hydrogen integrated energy system with virtual energy storage - Liu, Xinghua (2024)
In this paper, a model of electricity hydrogen integrated energy system considering virtual energy storage is proposed to enhance the penetration rate of renewable energy. Specifically, mathematical modeling is conducted for the integrated energy system of electricity hydrogen. Considering the thermal characteristics of buildings and demand response from users, the virtual energy storage system is integrated into the model to optimize the system's overall performance. A day-ahead and intra-day optimization scheduling strategy is proposed to address the uncertainties of renewable energy generation, load forecasting, and power fluctuations. The day-ahead optimization model coordinates the output of various components to minimize the daily operating costs, resulting in a 24-hour operational plan. The intra-day scheduling model aims to smooth out power fluctuations and improve system stability by refining the day-ahead strategy through rolling optimization. Four comparative cases are presented to validate the proposed model. The quantitative results of this study show that introducing a virtual energy storage system has multiple significant advantages in an electric hydrogen integrated energy system. By optimizing operational costs, the equipment cost of the system is significantly reduced, and the integration of renewable energy is dramatically improved, effectively promoting sustainable development. In addition, the application of virtual energy storage maximizes the advantages of hydrogen energy while helping to reduce carbon emissions, providing strong support for the future sustainability of the energy system.